Expressing Frustration Online: Examining Indonesian Instagram Comments on National Football Team Reacting to Football Defeats Through Culpeper’s Impoliteness Framework - Ginting, Hestika; Fitriany, Fitriany (Faculty of Tarbiyah nad Teacher Training, 2025)
This study aims to analyze the impoliteness strategies used by Indonesian fans on instagram reacting to national team defeats. This research used a descriptive qualitative approach. The data from this study are impolite strategies taken from Indonesian instagram comments on Timnas (Indonesian National Football Team) instagram. The results of the study showed that only four types of impoliteness strategies presented in the comments by the football fans on Indonesian Football National Team (Timnas) Instagram. The strategies are bald on-record impoliteness, positive impoliteness, negative impoliteness, and sarcasm or mock politeness. Bald on-record impoliteness was dominantly used in the comments. The study also found that most of the impoliteness comments were aimed at the coach, appealing for his dismissal.